Diabetes is an independent predictor of right ventricular dysfunction post ST-elevation myocardial infarction. Issue 1 (December 2016) - Roifman, Idan; Ghugre, Nilesh; Zia, Mohammad; Farkouh, Michael; Zavodni, Anna; Wright, Graham; Connelly, Kim
Abstract Background Diabetes mellitus (DM) is estimated to become the 7th leading cause of death by 2030. Right ventricular dysfunction (RVD) complicating ST elevation myocardial infarction (STEMI) is independently associated with a higher mortality; however the relationship between DM and RVD is currently unknown. The purpose of this study was to determine whether DM is an independent predictor for the presence of right ventricular dysfunction (RVD) post STEMI. Methods 106 patients post primary PCI for STEMI were enrolled in the study. Cardiac MRI was performed within 48–72 h after admission in order to assess ventricular function. Statistical analysis consisted initially of descriptive statistics including Chi square, Fisher's exact, or the Wilcoxon rank sum as appropriate. Subsequently, logistic regression analysis was performed to determine independent predictors of RVD. Results The median age in the study was 58 years (IQR 53, 67). 30 % of the patients had diabetes. Of 99 patients for which RV data was available, 40 had RVD and 59 did not. Patients with DM were significantly more likely to have RVD when compared to those without diabetes (45 vs 22 %, p = 0.03). There was no significant difference in age, hypertension, smoking status, dyslipidemia, serum creatinine or peak CK levels between the two groups. After adjusting for other factors, presence of DM remained an independent predictor for the presence of RV dysfunction (OR 2.78, 95 % CI 1.12, 6.87, p = 0.03). Amongst diabetic patients, those with HbA1C ≥ 7 % had greater odds of having RVD vs those with HbA1C < 7 % (OR 5.58 (1.20, 25.78), p = 0.02). Conclusions The presence of DM conferred an approximately threefold greater odds of being associated with RVD post STEMI. No other major cardiovascular risk factors were independently associated with the presence of RVD.